Cells, Cells and Nothing but Cells: Discoveries, Challenges and Directions - Kalyuzhny, Alexander (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The forum is for scientists doing research in different fields of cell science including, but not limited to, stem cells, autophagy, aging, intracellular organelles, proteomics, genomics, metabolism, and cell physiology. The goal of the symposium was to bring scientists together to facilitate the exchange of data and novel ideas to advance cell science as well as discussing the challenges facing cell biologists.